O processo de ensino aprendizagem através da gamificação na formação de acadêmicos das Ciências da Natureza no Programa Institucional de Bolsa de Iniciação à Docência (PIBID) - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The study of active methodologies, especially gamification, has shown to rise in the scientific world. Given this scenario, the present work has the main objective to verify if games and gamification as an active methodology in interdisciplinary didactic sequences can be facilitators in the teaching process. The research was situated in the domains of the quality-quantitative approach, outlined as descriptive, with collaborative research objectives. Content analysis was used to analyze the qualitative data and descriptive statistics for the other data. A study carried out with a group of scholarship holders from the Institutional Teaching Initiation Scholarship Program (PIBID), a program that aims to articulate primary education with higher education, inserting students in public schools located in peripheral areas, a game and gamification course in two steps: Step 1 - Context Analysis: To obtain an overview of the participants' prior knowledge, impressions about the use of games in the educational environment were collected through a questionnaire. Step 2 – Four synchronous meetings lasted one hour, where an explanation was given about games, their use, and the possibility of using them with pedagogical intentions, starting from the Didactic Sequences. Participants planned the gamification of the interdisciplinary didactic sequences built by the teachers at the researched school and made games, applied these constructions to 6th and 8th-grade students, and shared their impressions in a conversation circle. The research objectives were to verify the use of games and gamification in initial training, apply it in the school context with gamified DS, and collect participants' impressions on how much use of the tools was achieved, with participants' engagement and encouragement to face the virtual class regency, the need to constantly search for a motivating and contextualized teaching practice using active methodologies, as they ensured a more dynamic and meaningful teaching and learning process, bringing the teacher/student relationship closer and promoting the development of effective interdisciplinary practices.
The teaching-learning process through gamification in the formation of academics of Natural Sciences in the Institutional Scholarship Program for Teaching Initiation (PIBID)
Keywords: Gamificação; Jogos; Sequência didática; Metodologias ativas; Gamification; Games; Didactic sequence; Active methodologies; Língua Portuguesa; Ciências da Natureza; Portuguese language; Natural Sciences; CNPQ::CIENCIAS HUMANAS